2014
DOI: 10.1016/j.repc.2014.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Holt-Oram syndrome: A case report

Abstract: Holt-Oram syndrome is clinically characterized by morphological abnormalities of the upper limbs and congenital cardiac defects. Although the disease is congenital, the diagnosis may only be made later in life. It is a rare autosomal dominant disorder, caused by a mutation in the TBX5 gene located on chromosome 12, but sporadic cases have also been reported. We describe the case of a 75-year-old man with known morphological alterations of the upper limbs since birth and congenital cardiac defect (atrial septal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…According to previously studies, spontaneous closure occurs frequently in young patients (diagnosis at younger than 1 year) with small defects (size ≤ 8 mm) [ 1 ]. However, in many patients with a genetic syndrome with ASD, defects do not close spontaneously, most of them remain unchanged, even increased, especially in those mutations in genes essential to cardiac septation such as Holt–Oram syndrome ( NKX2-5 mutation) [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to previously studies, spontaneous closure occurs frequently in young patients (diagnosis at younger than 1 year) with small defects (size ≤ 8 mm) [ 1 ]. However, in many patients with a genetic syndrome with ASD, defects do not close spontaneously, most of them remain unchanged, even increased, especially in those mutations in genes essential to cardiac septation such as Holt–Oram syndrome ( NKX2-5 mutation) [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…TBX5 mutation was detected only in 74% of HOS affected individuals. [ 6 ] There were no TBX5 gene mutations in both of the cases.…”
Section: Discussionmentioning
confidence: 97%
“…[ 4 5 ] However, sporadic cases have also been reported. [ 6 ] Upper limb abnormalities, such as phocomelia and minor thumb anomalies are also observed in all patients. In 50-95% of patients ostium secundum type ASD, VSD, patent ductus arteriosus, heart block, and disorders such as Wolff–Parkinson–White syndrome are observed.…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 17 Hip dysplasia is a congenital malformation previously reported in only one patient with HOS, 6 due to hip malformation being an isolated sign of HOS, it is proposed as a random association and does not eliminate the diagnosis to HOS, as some authors have suggested in previous studies. 2 , 25 …”
Section: Discussionmentioning
confidence: 99%